PENGARUH PEMBERIAN REWARD DAN REINFORCEMENT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS V - Reflina Sinaga; Rudolf Rejekki Sitohang; Bogor Lumbanraja (JS (JURNAL SEKOLAH), 2023)
Abastract: This study aims to determine the effect of giving rewards and reinforcement on student learning outcomes in mathematics in class V at SDN 064981 Medan Helvetia for the 2021/2022 academic year. In this study, researchers used quantitative methods. The population used is all SDN students. 064981 Medan Helvetia with a sample of 61 students. Sampling using non-probability sampling. The results of this study indicate that the results obtained from the correlation test can be seen in the correlation coefficient of r (count ) 0.279 r〗_(table ) 0.254, it can be concluded that the alternative hypothesis (Ha) is accepted, that is, there is a significant effect between reward and reinforcement. on the learning outcomes of SDN students. 064981 Helvetia Field. It can also be seen from the results of the t-test where t_(count )> t〗_(table ) is t_(count ) of 2.234 and t〗_(table ) of 2.000, then the hypothesis (Ha) is accepted. This shows that there is a significant positive effect between the provision of rewards and reinforcement and mathematics learning outcomes in class V SDN. 064981 Medan Helvetia for the 2021/2022 academic year. Keywords: Reward and Reinforcement, Learning Outcomes. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh bpemberian reward dan reinforcement terhadap hasil belajar siswa pada mata pelajaran matematika kelas V di SDN 064981 Medan Helvetia tahun pembelajaran 2021/2022. Pada penelitian ini peneliti menggunakan metode kuantitatif. Populasi yang digunakan yakni seluruh siswa SDN. 064981 Medan Helvetia dengan sampel yang berjumlah 61 siswa. Pengambilan sampel dengan menggunakan nonprobability sampling. Hasil penelitian ini menunjukkan bahwa hasil yang diperoleh dari pengujian korelasi dapat dilihat pada koefisien korelasi sebesar  0,279 ≥ 0,254 maka dapat disimpulkan hipotesis alternatif (Ha) diterima yaitu terdapat pengaruh yang signifikan antara pemberian reward dan reinforcement terhadap hasil belajar siswa SDN. 064981 Medan Helvetia. Dapat juga dilihat dari hasil pengujian uji-t dimana >  yaitu sebesar 2,234 dan sebesar 2,000, maka hipotesis (Ha) diterima. Hal ini menunjukkan bahwa adanya pengaruh positif yang signifikan antara pemberian reward dan reinforcement dan hasil belajar matematika di kelas V SDN. 064981 Medan Helvetia tahun pembelajaran 2021/2022. Kata Kunci: Pemberian Reward dan Reinforcement, Hasil Belajar.